Challenges for private law in the 21st century - Burrows, A (University of Queensland, 2016)
After briefly looking at one aspect of the challenge posed for private law by ever-increasing legislation, this paper considers two of the main challenges for private law in the 21st century. First, in the face of signs of decline, how does one keep private law alive and thriving in the universities? One central suggestion made is that it is important to re-emphasise the merits of doctrinal/practical analytical research. Secondly, how might one address the non-accessibility of private common law? Here the paper discusses the on-going project to produce Restatements of the English Law of Obligations.